Caracterização de modelos de experimentação baseados na Doença de Alzheimer em zebrafish - Nery, Laura Roesler (2015)
New animal models for neurodegenerative diseases study are necessary for the knowledge of molecular mechanisms and behavioral patterns involved on the progression of dementias as Alzheimer’s Disease (AD) as well as for new therapies development. We characterized four neurodegenerative approaches including: (1) ß-amyloid(1-42) peptide injection, one of the hallmark proteins of patients with AD. In this model, we observed that intra-ventricular brain injection of ß-amyloid soluble oligomers in 24hpf embryos caused an increase in tau phosphorylation followed by cognitive deficits at 5dpf, both results being reversed by Lithium treatment, a tau kinase (GSK-3ß) inhibitor. (2) The inhibition of exon 8 splicing of Presenilin-1, protein responsible for the Amyloid Precursor Protein (APP) cleavage, was achieved using Morpholino oligonucleotides. This approach caused a dysfunction of Presenilin-1, characteristic of patients with the familiar form of AD, that disturbed cognitive behavior and caused morphological phenotype similar to the ones observed by modifications of Notch pathway. We also developed two transgenic animals, (3) one overexpressing through a heat-shock promoter the ß-amyloid protein. These animals when exposed to a temperature of 37ºC activate the heat-shock protein expression and as a consequence amyloid-ß protein, one of the hallmark proteins of AD. The second transgenic animal (4) we knocked-out the Appb gene using TALEN as a genetic manipulation technic. This model will provide a better understanding of Appb function during animal development and AD progression. Those four animal models include features suggesting that, when used separately or in combination, can hereafter elucidate those pathways interactions and clarify the cellular and molecular mechanism associated with cognitive deficits during Alzheimer’s disease progression. With these models we were able to characterize zebrafish as a potential animal model, not just for understanding the role of those proteins over neurodegenerative process, but also on their normal functions in the system. Besides that, zebrafish have been used for a few years in pharmacological tests, and the development of animal models for Alzheimer’s disease as ours, make this animal a robust model for development of new treatments for this and other diseases.